1995
DOI: 10.1007/bf02635793
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous and nonaqueous microemulsion systems with a palm oil‐base emollient

Abstract: Microemulsions with a palm oil-based emollient, i.e., medium-chain triglyceride (MCT), and water or glycerol, stabilized by two oppositely charged ionic surfactants and a medium-chain alcohol, were investigated. The results showed that only the water-in-MCT or the glycerol-in-MCT microemulsions were prominent. The maximum solubilization of the MCT emollient was higher in cetyftrimethyI ammonium bromide, i.e., the positively charged surfactant that contained a nitrogen atom, than the negatively charged surfacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…However, the microemulsification of molecularly large and partially amphiphilic oils such as triglycerides is notoriously difficult. Careful studies of the phase behavior of triglycerides with nonionic surfactants have consistently shown the existence of persistent asymmetric lamellar phases that solubilize very little oil. While patents and reports abound that claim the microemulsification of triglycerides using a wide variety of surfactants, there have been no reports of triglyceride microemulsions that exhibit the characteristic patterns of nonionic surfactant phase behavior 27 and which allow precise control of the phase behavior and microstructure ranging from water-continuous to bicontinuous to oil-continuous. Minana-Perez et al have previously reported the use of alkyl sulfates with oxypropylene groups inserted between the sulfate headgroup and the alkyl tail for forming efficient microemulsions of the bicontinuous type.…”
Section: Introductionmentioning
confidence: 99%
“…However, the microemulsification of molecularly large and partially amphiphilic oils such as triglycerides is notoriously difficult. Careful studies of the phase behavior of triglycerides with nonionic surfactants have consistently shown the existence of persistent asymmetric lamellar phases that solubilize very little oil. While patents and reports abound that claim the microemulsification of triglycerides using a wide variety of surfactants, there have been no reports of triglyceride microemulsions that exhibit the characteristic patterns of nonionic surfactant phase behavior 27 and which allow precise control of the phase behavior and microstructure ranging from water-continuous to bicontinuous to oil-continuous. Minana-Perez et al have previously reported the use of alkyl sulfates with oxypropylene groups inserted between the sulfate headgroup and the alkyl tail for forming efficient microemulsions of the bicontinuous type.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In this effort, normal alkanes have been replaced by oils acceptable in food (or pharmaceuticals) industry, and the majority of preparations are oil continuous. These papers focused on studying the ability of formulating a microemulsion with triglycerides [9][10][11][12][13][14] and perfumes [15][16][17] as the oil component. Joubran and coworkers 18,19 have studied the phase behavior and microstructure of water-in-triglycerides (W/O) microemulsions based on polyoxyethylene (40) sorbitanhexaoleate.…”
Section: Introductionmentioning
confidence: 99%
“…From a food industry perspective, an ideal candidate for the formation of microemulsions is vegetable oil (due to its low cost and abundance). However, the most common organic phase used in microemulsions is mineral oil, which is a mixture of aliphatic chains with chain lengths normally varying from 8 to 30 carbons [40,41] ). Mineral oil has been used in microemulsions as it is effective at generating well-defined dispersed phases.…”
Section: Organic Phasementioning
confidence: 99%
“…[15] Many food-based oils including mineral, soy, corn, cottonseed and sunflower have been used to generate microemulsions, although not necessarily for food applications. [15,33,[40][41][42] Long-chain triglycerides (e.g., with 18 carbons) are difficult to solubilise given their high molecular weight which limits their flexibility at the interface and restricts film penetration and formation. [15] These have been often substituted by medium-chain triglycerides (e.g., tricaprylin), where the smaller fatty acid chain lengths permit greater flexibility at the interface.…”
Section: Organic Phasementioning
confidence: 99%
See 1 more Smart Citation